Assessment for the Quality of Recovery from general anaesthesia in patients undergoing laparoscopic surgery: An observational study - Deepti Kotwani; Manish B Kotwani; Prateek Agrawal (Journal of Krishna Institute of Medical Sciences University)
Background: Quality of recovery following major surgery is directly related to patient satisfaction. Out of numerous patient-based measures, a '40-item-quality of recovery (QoR-40)' has proved to be a valid and reliable scale which assesses five dimensions of post-surgical recovery: physical-comfort, emotional-state, physical-independence, psychological support, and pain. Aim and Objectives: To evaluate the quality of recovery and to study different factors influencing recovery after major laparoscopic surgery & anaesthesia using QoR-40 questionnaire. Material and Methods: This prospective observational study included 215 adult patients who were posted for laparoscopic surgery. Quality of recovery was assessed after 12 hours, using patient based QoR-40 questionnaire. Total score of QoR-40 questionnaire ranges from 40 to 200. Higher scores indicate better quality of recovery. Results: Out of total 215 patients, 142 (66%) had mean QoR-40 score of > 150. Mean QoR-40 score was higher after lower abdominal laparoscopy (159.00 ± 14.11) than after upper abdominal laparoscopy (155.32 ± 14.80) (p = 0.139). Shorter duration of surgery (< 120 minutes) had significantly higher QoR-40 scores (161.84 ± 13.92) than with longer duration (> 120 minutes) of surgery (152.28 ± 14.38) (p < 0.001). Mean QoR-40 scores were lower (148.07 ± 11.25) in patients who had post-operative complications. Conclusion: Quality of recovery following laparoscopic surgeries as predicted by QoR-40 questionnaire was influenced by duration of surgery, upper or lower abdominal laparoscopic surgery and post-operative complications. Type of anaesthetic drugs used had no significant effect on quality of recovery. However, since QoR is multifactorial, many co-variables need to be studied in a wider study population.